STUDI ANALISIS FUNDAMENTAL DALAM MEMBUAT KEPUTUSAN INVESTASI PADA PT. ADIRA DINAMIKA MULTI FINANCE Tbk - Nuraini, Siti (Profit : Jurnal Inovasi Ekonomi dan Bisnis, 2023)
This research aims to evaluate considerations for investment choices using fundamental analysis of financial reports for investment decision-making at PT Adira Dinamika Multi Finance Tbk for 2020-2022. Fundamental analysis measures intrinsic value as a consideration for making investment decisions. The method used to measure fundamental analysis is using information sources of Adira Finance company financial report data with measurement indicators using financial ratios such as Price to Earning (PER), Debt to Equity Ratio (DER), Dividend Payout Ratio (DPR), Dividend per share (DPS), Return on Investment (ROI), and Return on Equity (ROE). The results of this research show that based on the intrinsic value, market prices in 2020-2022 are unstable, where the condition of PT Adira Dinamika Multi Finance Tbk shares in 2020 is undervalued with investment decisions best made by buying shares, 2021 the share condition is overvalued with investment decisions should be made by not buying shares. In contrast, in 2022, the stock condition will again be undervalued, with investment decisions best made by buying shares